Preparation of a hydrogel from human fetal membranes for 3D cell culture - Deus, Inês Araújo (2019)
Recently, three-dimensional (3D) cell culture platforms have emerged as valuable tools with potential to increase the accuracy of in vitro studies. Inspired by the extracellular matrix (ECM) that compose living tissues, these platforms have been designed to support the attachment and growth of cells, therefore providing reliable data on how they behave and respond to stimulus when within their natural environments. Despite the great advances made on the design of such materials, including the development of ECM-based hydrogels such as Matrigel®, recapitulate the complexity and function of native ECMs, while producing cost-effective and safe materials, remains a challenge. METATISSUE is a start-up company founded in 2018 that intends to address this challenge by developing human-derived 3D cell culture platforms. Amniotic membrane (AM) is a placental tissue usually discarded after delivery, thus representing a readily available source of human ECM. Although this tissue has been widely explored in the formulation of scaffolds for tissue engineering, its formulation as a hydrogel has been highly limited by the poor mechanical properties of resulting materials. Therefore, the aim of this work was to develop a photopolymerizable hydrogel derived from human AM with tunable mechanical properties for application in 3D cell culture. Amniotic membrane was isolated from placenta, decellularized and solubilized to produce a solution rich in ECM structural proteins and growth factors, and free of cells. Amniotic membrane methacrylated (AMMA) was produced by reacting the previous solution with methacrylic anhydride in order to obtain two different degrees of modification: AMMA100 (low-modification degree) and AMMA300 (high-modification degree). Finally, AMMA hydrogels were successfully obtained upon irradiation with UV or visible light. AMMA hydrogels were characterized in terms of their biochemical, mechanical and biological properties. Although some ECM components were significantly reduced after processing of AM, the hydrogels obtained were robust and stable. Indeed, characterization studies revealed that were obtained hydrogels with tunable mechanical properties. In vitro assays using human adipose-derived stem cell (hASCs) and human umbilical cord endothelial cells (HUVECs) indicated that these materials were able to support growth of top seeding cells. The encapsulation of stem cells confirmed that AM hydrogels support adhesion, proliferation and invasion of this kind of cells. In sum, this work demonstrated that human AM-derived ECM can be efficiently functionalized with photorespondive groups to produce a versatile and robust hydrogel with potential to be used in 3D cell culture.